2007
DOI: 10.1007/s12028-007-9017-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Nicardipine for Refractory Cerebral Vasospasm after Subarachnoid Hemorrhage

Abstract: Our preliminary observations suggest that intraventricular nicardipine could be considered as a safe and effective treatment modality to treat vasospasm refractory to conventional management. A randomized, controlled trial to verify the efficacy and safety of intrathecal nicardipine in the prevention and treatment of cerebral vasospasm is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…However, the dose of 4 mg was diluted in 2 ml of preservative free saline instead of 10 ml to minimize the volume injected into the intraventricular space. This dosing is similar to that described by Goodson et al and Ehtisham et al [10,11]. The optimal concentration of nicardipine in the CSF is not known.…”
Section: Dayssupporting
confidence: 71%
See 2 more Smart Citations
“…However, the dose of 4 mg was diluted in 2 ml of preservative free saline instead of 10 ml to minimize the volume injected into the intraventricular space. This dosing is similar to that described by Goodson et al and Ehtisham et al [10,11]. The optimal concentration of nicardipine in the CSF is not known.…”
Section: Dayssupporting
confidence: 71%
“…Similar series have reported on the use of nicardipine prolonged release implants [12,13]. Recently, Goodson et al and Ehtisham et al [10,11] have reported their successful experience with intraventricular administration of nicardipine in patients with vasospasm refractory to conventional treatments. Intraventricular administration of nicardipine is particularly appealing in patients with aSAH as many of these patients have ventricular drains in place.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The safety and efficacy of intrathecal nicardipine for the prevention and treatment of SAH-induced vasospasm has been clearly demonstrated in the clinical setting [58,119,133,134,135,136,137,138,139,140]. Shibuya et al [135] reported the effects of prophylactic serial administration of intrathecal nicardipine on vasospasm in 50 Fisher grade III SAH patients.…”
Section: Novel and Alternative Therapies For Sah-induced Cerebral Vasmentioning
confidence: 99%
“…The drug was well tolerated, and 7 of the 8 patients had moderate to good functional outcomes. 118 A potential novel option for administering nicardipine is the insertion of nicardipine-releasing implants at the time of surgical intervention. A phase II prospective, randomized, double-blind evaluation of nicardipine prolonged release implants in 32 patients demonstrated that nicardipine was more effective than placebo at reducing the incidence of vasospasm (7% vs 73%; P < .05) and delayed cerebral ischemia (14% vs 47%; P < .05).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%